Дослідження питання моніторингу дій людей у приміщенні на основі аналізу відеопотоку з камер відеоспостереження - Ісаєв, Є. А. (ХНУРЕ, 2024)
This work is devoted to the study of the question of monitoring the actions of people indoors based on the analysis of the video stream from surveillance cameras with the aim of further developing a plugin for the iSpy application. Special attention is paid to the study of trackers from BoT-SORT, ByteTrack from the modern Ultralytics framework, as well as experiments with different variants of the YOLOv8 model, which is designed for detection and classification. The results of the research showed that it is reasonable to use the ByteTrack tracker with the YOLOv8n model for implementation in the iSpy application as the fastest tracker and one with high enough accuracy to accomplish the task.
Keywords: аналіз відеопотоку; камера відеоспостереження